Psychosocial factors associated with engagement and efficacy of mindfulness intervention in the classroom - Savannah K.H. Siew; Junhong Yu (PLoS ONE, 2026)
Background Mindfulness practice has been associated with a range of benefits in the literature. However, intervention effects show substantial person-to-person variability, and the individual differences underlying this variability remain underexamined. Identifying the psychosocial predictors of the practice can increase our understanding of the mechanisms underlying the benefits of mindfulness practice and inform strategies to increase both engagement and efficacy of it. Methodology 66 university students in Singapore were recruited if they had completed a course where mindfulness practice was conducted during the lecture. Participants were aged between 18–39 years old (Mage = 22.2 years). They completed an online survey measuring trait mindfulness, personality traits, attachment and conflict styles, intrinsic motivation, grit, and attention control. Outcome variables of engagement and efficacy were self-reported. Multiple linear regression for each independent variable controlled for different course taken and prior mindfulness experience using a multiple comparison corrected confidence interval of 99.8%. Results Intrinsic motivation was positively associated with both engagement in mindfulness practice and its usefulness. The observing facet of trait mindfulness, total trait mindfulness and conscientious personality were negatively associated with how difficult participants felt the mindfulness practice was. Discussion The significant psychosocial and cognitive variables associated with both engagement and efficacy of mindfulness practice from this exploratory study add to our understanding of the type of participants that might be more suited for mindfulness practice in the classroom.